Digital Credit Risk Management Training: An Introduction to Online Loans and Paylater Services for Generation Z - Fathihani, F.; Meutia, Kardinah Indrianna; Rahmat, R.; Ferdiyantoro, Suryo; Kurniati, Mira (Universitas Muhammadiyah Malang, 2026)
Generation Z, often referred to as the internet generation (iGen), born between 1997 and 2012, is a generation deeply immersed in technological advancements. The rapid development of technology across various financial sectors has meant that Generation Z is also a generation that is enjoying the shift from traditional financial services to digital financial services, such as online loans and paylater schemes. Online loans are services that make it easy for users to borrow money online, whilst paylater schemes allow users to obtain the products or services they desire first and make payment at a later date. The rising incidence of non-performing loans in online lending and paylater services is driven by materialistic tendencies such as compulsive buying, a propensity for debt, and ‘flexing’, as well as the phenomenon of Fear of Missing Out (FOMO) – the fear of appearing outdated on social media – which often leads Generation Z to view online lending as a quick alternative to sustain their lifestyle. Given this urgency, this Community Service (PkM) activity aims to enhance Generation Z’s understanding of digital credit risks through financial risk management training, an introduction to the mechanisms of online loans and paylater services, and the fostering of wiser financial behaviour. The partners for this activity are students from SMK Budi Perkasa in the Tambun area of Bekasi. The implementation of the PkM comprises three stages: preparation, implementation, and evaluation. The outcomes of the ‘ ’ PkM activity were evaluated using pre- and post-tests, and the results indicate that interactive and practical training is highly effective in enhancing participants’ knowledge of digital credit risk management. Overall, this PkM activity successfully achieved its set objectives and had a positive impact on changes in students’ financial knowledge and attitudes.